Analysis of The Effect of Using Google Gemini as an AI Tutor on Students' Digital Literacy Skills and Learning Outcomes in Science and Social Sciences Subjects - Rizal Bakti; Erliza Septia Nagara; Syaadiah Arifin; Nurohim Nurohim; Jumriah Jumriah (EduInovasi: Journal of Basic Educational Studies, 2026)
The integration of artificial intelligence (AI) in education has opened a new paradigm, one of which is through the use of large language model platforms such as Google Gemini as a personal tutor for students. This study aims to analyze the effect of using Google Gemini as an AI Tutor on digital literacy skills and student learning outcomes in Natural Sciences (IPA) and Social Sciences (IPS) subjects. Using a quantitative explanatory approach, this study involved a sample of high school students divided into an experimental group (using Google Gemini) and a control group (using conventional methods). Data were collected through digital literacy ability tests, pre- and post-test IPA and IPS learning outcome tests, and student perception questionnaires. The results of the statistical analysis showed that the use of Google Gemini significantly improved students' digital literacy skills, especially in the dimensions of critical information retrieval and AI-based content evaluation. In addition, there was a significant increase in learning outcomes in both exact science subjects and contextual-analytical IPS subjects, when compared to the control group. Interestingly, students in the IPS subject showed higher problem-solving efficiency, while students in the IPS subject showed better depth of critical analysis after interacting with the AI ​​Tutor. This study concludes that Google Gemini effectively functions as a cognitive accelerator, bridging conceptual understanding gaps while simultaneously training students' digital skills. The implications of this research emphasize the need for integrated regulations and curricula to ensure that the use of generative AI in schools prioritizes academic ethics and independent thinking.